An Analysis of Laskar Pelangi Novel by Using Biographical Criticism - TUSSADIAH, HALIMAH (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research showed that the biography of the author directly attached and gave an overview of the actual content of the novel. It was found in the relationship between Andrea Hirata as an author with his work entitled Laskar Pelangi. The objectives of this research were to find out the theme of the novel and the relationship between Laskar Pelangi novel and the life of Andrea Hirata. Descriptive qualitative method was carried out to analyze the data. The source of the data was taken from the novel Laskar Pelangi by Andrea Hirata. In collecting the data, some references related to Biographical criticism were applied. The data were analyzed by reading, analyzing and describing the content of the novel. It was concluded that the theme was the comlexity of the life of Ikal who was the representative of the author himself; they comprised 6 data dealing with the theme of the novel (social and cultural theme, religious theme, economical theme and educational theme) and 38 data related to his biography., It was proved that there was the relationsip between the author wih the content of Laskar Pelangi novel.